Level of Pedagogical Competence of Madrasah Ibtidaiyah Teachers in Palembang City - Ahmad Zainuri (Jurnal Madania)
The purpose of preliminary research is to describe the level of pedagogical competencies of State Islamic Elementary School (MIN) teachers in Palembang City. This type of research is quantitative research with an explorative approach and data analysis through descriptive statistics. Based on the results of the study with a sample of 85 teachers at the MIN City of Palembang, it is found that nine pedagogical dimensions are still in the sufficient category, where the mean score is 281.03. The only dimensions of pedagogic competence in a good category are utilizing information and communication technology for the benefit of learning. Based on these results, it is necessary to increase the dimensions of teacher pedagogical competencies to be better because teachers who have good pedagogical competence are one of the factors in motivating and influencing student learning outcomes. Through this research, it is expected that it can be used as a reference for interested parties and also for further researchers in improving teacher competencies, especially pedagogical competencies.